Holocene land cover change in the Pannonian (East-Central Europe) forest steppe: The role of prehistoric land exploitation phases - Ilona Pál; Enikő K. Magyari; János Korponai; Gábor Mesterházy; Ákos Bede-Fazekas; Cristina Covătaru; Gabriella Darabos; Gusztáv Jakab; András Füzesi; Pál Raczky (Quaternary Environments and Humans, 2025)
Pollen analytical studies of Holocene lake and mire sediments provide valuable information on past forest cover changes and help us resolving the long-debated origin of temperate forest steppes in Europe. In this paper we contribute to this debate via the pollen and multi-proxy palaeoecological (macrofossil, charcoal, major and trace element) analyses of a paleolake (Kokad Mire) situated in the temperate deciduous forest steppe zone of the Great Hungarian Plain (GHP). Diverse soil types and microhabitats in this area attracted arable farming communities since the Neolithic. By comparing the local archaeological record with the pollen-based land cover, vegetation composition and fire history changes, and invoking other pollen-based Holocene land cover records from the GHP, we analyze the climatic versus anthropogenic origin of the forest steppe vegetation, determine the ages of significant forest clearance episodes, and examine the relationship between paleo-proxy inferred land use and prehistoric/historic settlement density. Our results suggest that the current potential forest steppe vegetation of the eastern GHP had natural climatic and edaphic origin in the Early and Mid-Holocene, which was maintained by anthropogenic deforestation in the Late Holocene. Without human impact, forest cover must have increased during the last 3000 years, and likely even earlier, since the Early Bronze Age. We found evidence for episodic land use during the Neolithic: Middle and early Late Neolithic (7600–7400 cal BP) coppice management and pastoral farming. Deforestation intensified from 3900 cal BP (during the Bronze Age). We demonstrated very early hemp (Cannabis sativa) cultivation between 5970–5450 cal BP (Middle Copper Age) likely attributable to eastern nomadic pastoral groups (pre-Yamnaya) who left behind several burial mounds in the region. We also showed that the lake was used for hemp retting between 2450–2000 cal BP by the local Celtic groups. The analysis of three pollen records from the GHP furthermore revealed that prehistoric cultures had different occupation intensities until the Late Bronze Age with localized forest clearances followed by afforestation.